Morphological and Morphometric Analysis of Reticulated Python (Malayopython reticulatus) Crossbreeds within the Snake Enthusiast Community - Adhaeni, Nicky Utami; Mujadid, Iqbal; Hadi, Nestiyanto; Ainy, Noer Sarifah; Supriyadi, Erwandi (Biology Education Study Program, Faculty of Teacher Training and Education, University of Mataram, Indonesia, 2026)
This study aimed to analyze the morphological and morphometric characteristics of hybridized reticulated pythons (Malayopython reticulatus) in the Tabu Indonesia Community, Cimanggis–Depok. The research used a quantitative descriptive method through direct observation of morphological characters and morphometric measurements of hybrid pythons. The observed characters included color patterns, head shape, scale arrangement, body length, tail length, and the number of certain scales. The results showed variations in the morphological and morphometric characteristics of hybrid reticulated pythons, particularly in dorsal patterns, color intensity, body size, and the number of ventral and subcaudal scales. These variations were influenced by genetic combinations of the parent stock and environmental factors during captivity. This study concluded that hybridized reticulated pythons in the Tabu Indonesia Community, Cimanggis–Depok possess relatively high phenotypic diversity. The results are expected to provide scientific information regarding the morphological and morphometric characteristics of hybrid reticulated pythons in Indonesia.